Physical Activity Recommendations in the Context of New Calls for Change in Physical Education - Frömel, Karel; Vašíčková, Jana; Skalik, Krzysztof; Svozil, Zbyněk; Groffik, Dorota; Mitáš, Josef (International journal of environmental research and public health, 2021)
The current social, health, and educational changes in society require an adequate response in school-based physical activity (PA), including physical education (PE) lessons. The objective of this study was to identify the real average step counts of Czech and Polish adolescents during PE lessons, and propose recommendations for improving PE programs. This research was carried out in 143 Czech and 99 Polish schools. In the research, a total of 4911 adolescents aged 12-18 years were analyzed as part of teaching practice and 1827 in the context of habitual school practice. Steps were monitored using pedometers. The average step count per PE lesson was 2390 in Czech and Polish boys, while girls achieved 1851 steps. In both countries, boys were subject to greater physical strain in PE lessons compared to girls, both in teaching practice (F(4088,3) = 154.49, p < 0.001, ηp2 = 0.102) and school practice (F(1552,3) = 70.66, p < 0.001, ηp2 = 0.103). Therefore, the priority in PE lessons is to increase the amount of PA for girls, achieve the objectives of PE during PA, and use wearables to improve awareness of PA and improve physical literacy, as well as to support hybrid and online PE as a complement to traditional PE.
Keywords: wearables; Male; Polsko; Physical Education and Training; Schools; aktigrafie; Humans; pandemic; mužské pohlaví; Exercise; Female; mladiství; tělesná výchova; steps; ženské pohlaví; Actigraphy; recommendation; školy; cvičení; Poland; Adolescent; lidé; dítě; online physical education; Child